Pengaruh Financial Distress, Company Growth, dan Firm Size Terhadap Opini Audit Going Concern - Pascalis Nicholaz Ignatio Saka; Sophia Andini (UNIVERSITAS KALBIS, 2022)
This study aims to analyze the effect of financial distress, company growth, and company size on ongoing concern audit opinion. Going concern audit opinion is an expression given by the auditor to an entity because the auditor doubted the sustainability of the company's business. In conducting sample selection, researchers used a purposive sampling method that obtained a sample of 36 companies from 180 observations. The data analysis method used in this study is logistic regression using Eviews version 9. The population in this study are all manufacturing companies of consumer goods sectors listed on the Indonesia Stock Exchange (BEI) in 2014 - 2018. Partial test results show that financial distress, company growth, and company size effected a going-concern audit opinion.